2020
DOI: 10.1002/alr.22524
|View full text |Cite
|
Sign up to set email alerts
|

Association of the sinonasal bacterial microbiome with clinical outcomes in chronic rhinosinusitis: a systematic review

Abstract: Background:The association between sinonasal microbiome and clinical outcomes of patients with chronic rhinosinusitis (CRS) is unclear. We performed a systematic review of prior studies evaluating the CRS microbiome in relation to clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
(203 reference statements)
1
9
0
Order By: Relevance
“…Emerging evidence shows that different microbiome varied in their associations with clinical symptoms of patients with chronic rhinosinusitis ( Wang et al, 2020 ). Few studies have explored the changes in salivary microbiomes of HNC patients with HNC-related symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence shows that different microbiome varied in their associations with clinical symptoms of patients with chronic rhinosinusitis ( Wang et al, 2020 ). Few studies have explored the changes in salivary microbiomes of HNC patients with HNC-related symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Multiple hypotheses have been proposed to explain the potential mechanism of Th1-Th2 imbalance, leading to the development of rhinitis, but so far the precise influence of biodiversity changes in CRS remains unexplained. [22][23][24][25][26][27] Nevertheless, increased bacterial dysbiosis, characterized by a reduction in microbial diversity, has been reported in patients with CRS compared with healthy patients.…”
Section: Discussionmentioning
confidence: 99%
“…While CRS is by definition considered to be driven by chronic inflammation of the nasal mucosa, the role of dysbiosis was raised as a potential driving factor of the inflammatory mechanisms . Multiple hypotheses have been proposed to explain the potential mechanism of Th1-Th2 imbalance, leading to the development of rhinitis, but so far the precise influence of biodiversity changes in CRS remains unexplained . Nevertheless, increased bacterial dysbiosis, characterized by a reduction in microbial diversity, has been reported in patients with CRS compared with healthy patients.…”
Section: Discussionmentioning
confidence: 99%
“…43 Variations in the microbiome have been associated with differences in symptom severity and are predictive of surgical outcomes. 44 Furthermore, one retrospective analysis of sinonasal cultures taken during ESS found that males had a higher rate of Staphylococcus and anaerobes. 45 More research is needed to better understand the role of the microbiome in CRS pathogenesis, how the microbiome differs by gender, and its relationship with outcomes.…”
Section: Discussionmentioning
confidence: 99%